2006
DOI: 10.1002/cncr.22341
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen nadir within 12 months of prostate cancer radiotherapy predicts metastasis and death

Abstract: Objective: The main goal of this study was to verify the influence of low birth weight (LBW) on the physical fitness of children aged 7–10 years. The comparisons were subsequently adjusted for chronological age, gender, physical activity (PA), and body composition. Methods: A total of 356 children of both genders born in Vitoria de Santo Antão (Northeast of Brazil) were divided into two groups according to their birth weight (LBW < 2.500 g, n = 100, and normal birth weight, NBW ≥ 3.000 g and ≤ 3.999 g, n = 256… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 67 publications
6
33
0
Order By: Relevance
“…Although a longer follow-up is needed to confirm the results of SBRT in monotherapy or preboost modality for LpC, the data are encouraging and confirm the results obtained with HDR. 22,23 In another study, 19 a cohort of 38 patients with LpC, including 20 treated with SBRT monotherapy (38 Gy/4 fractions) and 18 with a post-EBRT boost (19 Gy/2 Fx) were described. The data observed were comparable to ours both in terms of toxicity and in terms of PSA control.…”
Section: Discussionmentioning
confidence: 99%
“…Although a longer follow-up is needed to confirm the results of SBRT in monotherapy or preboost modality for LpC, the data are encouraging and confirm the results obtained with HDR. 22,23 In another study, 19 a cohort of 38 patients with LpC, including 20 treated with SBRT monotherapy (38 Gy/4 fractions) and 18 with a post-EBRT boost (19 Gy/2 Fx) were described. The data observed were comparable to ours both in terms of toxicity and in terms of PSA control.…”
Section: Discussionmentioning
confidence: 99%
“…Although much effort has been placed on the importance of pretherapy PSA doubling time (1), less information is available regarding the possible importance of PSA response after therapy. Retrospective reviews from the Fox Chase Cancer Center (3,4) have demonstrated that posttherapy PSA can predict for long-term outcome reporting that the level of the PSA nadir was predictive of OS and metastatic free survival. Denham et al (5) recently reported on PSA response signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Posttreatment PSA has also shown to be important. Several reports have discussed the prognostic information of posttreatment PSA, including nadir level (2)(3)(4), time to nadir, and PSA response signatures (5).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of distant metastases at 10 years were 4 per cent (PSA ≤2ng/ml) or 19 per cent (PSA >2ng/ml). 20 Horwitz et al (2005) studied this cohort postradiotherapy. Biochemical failure was defined as 2-3ng/ml greater than nPSA or two consecutive rises of at least 0.5ng/ml.…”
Section: Psa Post-radical Radiotherapymentioning
confidence: 99%